Marco teórico: la colaboración Universidad-Industria - Gutiérrez, Ernesto; Ribeiro de Aguiar, Sérgio; Aisa, Silvia; Macedo dos Santos, Raimundo Nonato; Talbot, María Lorena (Universidad Nacional del Litora, 2024)
Fil: Macedo dos Santos, Raimundo Nonato. Universidade Federal de Pernambuco; Brasil.